ETIKA UPACARA BALIATN PEMBENTUK KARAKTER MASYARAKAT HINDU DAYAK DEAH - Soharsono; Sukarma, I Wayan; Ariastina, I Gusti Putu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Before the teachings of Hinduism came, Monotheism and Monism had already developed in Indonesia, among the native population, a belief system called Animism and Dynamism. This belief is still implemented and believed to this day. We can see the belief in animism and dynamism in the Dayak Deah ethnic group who still practice healing methods of illness in the form of ceremonies (rituals), namely Beliatn. The Beliatn ceremony is included in the Human Yadnya ceremony. The Beliatn ceremony is only carried out by the Dayak tribe who adhere to the Hindu religion. The implementation of the Beliatn ceremony by the Dayak Deah tribe is only understood as a belief passed down from generation to generation in the form of entrenched traditions, without understanding the religious meaning including ethical values. Because scientific research into the Beliatn ceremony has not been carried out to an essential extent. Based on this, to find out, the implementation of the Beliatn ceremony in terms of facilities, place and time, the ceremony leader, the series of implementation, what ethical education is during the implementation of the Belitan ceremony, what is the perception of the ethical education aspects in the ceremony. This research uses qualitative methods, processing data by compiling it systematically, emphasizing analysis on descriptive data in the form of observed written words. The analysis of this data is more focused on library research, namely by reading, studying and examining books and written sources that are closely related to the problem being discussed. Related to the educational value of Baliatn Ceremony ethics in Hinduism. with research subjects carried out in Mangcupuk Village, Muara Uya District, Tabalong Regency. Through the results of this scientific research, conclusions can be drawn as to the main problem. The Beliatn ceremony uses facilities in the form of food containers, ceremonial equipment and musical instruments, and is led by a Mulukng assisted by a Penggadikng in charge of arranging the upakara/offering facilities during the ceremony. The series of Beliatn ceremonies consist of; Ngontah ceremony (initial ceremony), Besurah (deliberation), Netungkal ceremony (cleaning), Metanja ceremony (sacred dance), and Ngator ceremony (final ceremony). Rituals in the form of Belian ceremonies are not only for curing illnesses, but also as a medium for instilling educational values ​​of Ceremonial, Religious and Social Ethics which they call the Wolupm custom.